Assessment of grass roots irrigation water conflicts through governorates' profiles - Aboul-Fotoh N.Z.; Eddin Abdin A.; Sedky S. (Water culture and water conflict in the Mediterranean area, 2008)
In Egypt, water is increasingly becoming a national stability and security issue. Water disputes today are most evident when it comes to irrigation water which accounts to 84 percent of all water consumption. Water conflict is commonly taking place at the village, inter-village, regional, and national levels, as well as at the inter/intra institutional and local/institutional level. Some of these have the potential of developing into social and political destabilizing factors. The current research paper is aimed towards addressing these conflicts' issues within the grass roots of water users. Specifically, this study assesses, profoundly, the entire characteristics of irrigation water conflicts in four Egyptian governorates, Fayoum, Sohag, Kafr El-Shiekh, and Aswan, as pilot case studies. The identification of these conflicts' characteristics is performed through comprehensive and detailed governorates' profiles within all four pilot areas. The results of this intensive field research revealed detailed findings about the nature and history of conflicts, effects of conflicts, parties to the conflicts, root causes of the conflicts, dynamic of conflicts, and alternatives to conflict management.
1. MELIA Workshop Water Culture and Water Conflict, 2007/11/22-25, Nabeul-Médenine (Tunisia)